Barber Booking Mobile Application - Krishnan, Sivaneeswaran; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2024)
Barbers offer haircuts and trimming to customers at the barbershop. Barbers traditionally offer haircuts and trimming on a first-come, first-served basis. However, this can lead to long queues and a disorganized process. To address this, a mobile application called "Barber Booking Mobile Application" was developed. The application allows customers to book their time slots in advance, view prices, and make payments through online banking. This streamlines the booking process for both customers and barbers and provides a more efficient and organized experience for everyone involved. The application was developed using the Scrum methodology and object-oriented approach. It is accessible via an Android mobile device and is used by both customers and barbers. The overall outcome of the Barber Booking Mobile Application is a more efficient and organized process for barbershops, enhanced customer experience, and improved customer and appointment management.